Technical And Scale Efficiency Of Domestic And Foreign -owned Commercial Banks In Malaysia: A Data Envelopment Analysis - Abd. Kadir, Hazlina (2003)
The recent financial crisis of 1997 which had a significant adverse effect on the financial institution in Asia, had certainly raised everyone's awareness of the weakness of the Asian financial system. The focus of this paper is to test evidence of technical and scale efficiency in the commercial banking sector in Malaysia. In this context , the study attempts to evaluate if there are any differences in the efficiency of domestic and foreign owned Malaysian banks. This is done by applying the nonparametric Data Envelopment Analysis(DEA) for 29 commercial banks in Malaysia from 1994 to 1999.